A stabilizer composition for new energy vehicle charging pile power cord and preparation method thereof
By using hydrotalcite, perfluorohexanoic acid modified chitosan and other components in PVC charging cables, the problem of aging of traditional materials at high temperatures is solved, and the high temperature of PVC cable materials is achieved Improved stability and long-term performance.
Patent Information
- Application Number
- CN202411055625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-02
AI Technical Summary
Traditional polyvinyl chloride charging cables age under high temperature conditions, resulting in a decrease in the tensile strength of the material and the tensile strain of the breaking, which cannot meet the high-temperature stability and long-term performance requirements of the power cord of the charging pile of new energy vehicle.
Using a stabilizer composition, including hydrotalcite, perfluorohexanoic acid modified chitosan, beta-dione, alkaline metal compounds, hindered phenolic antioxidants, phosphite compounds and polyol compounds, Through specific proportions and preparation methods, stable chelate and graft structures are formed to improve the thermal stability of polyvinyl chloride cable materials.
Effectively control the tensile strength change rate and tensile strain range of polyvinyl chloride cable material at high temperature, extend the service life of the material and improve safety performance, and meet the high-temperature stability requirements of the power cord of charging piles of new energy vehicles .
Smart Images

Figure BDA0004976303540000111 
Figure BDA0004976303540000112 
Figure BDA0004976303540000121
Abstract
Description
Technical Field
[0001] The present invention relates to a stabilizer composition and a preparation method thereof, and in particular to a stabilizer composition for a power cord of a charging pile of a new energy vehicle and a preparation method thereof. Background Art
[0002] With the vigorous development of the global new energy vehicle industry, charging piles are the key infrastructure for charging electric vehicles, and their performance stability and safety are particularly important. In the new energy vehicle charging pile system, the power line, as a bridge connecting the charging pile and the electric vehicle, must not only withstand the transmission requirements of high current and high voltage, but also maintain long-term stable performance under a variety of complex environmental conditions, especially in high temperature environments.
[0003] As a widely used cable insulation material, polyvinyl chloride (PVC) plays an important role in the manufacture of power cables for new energy vehicle charging piles due to its good insulation, processability and economy. However, traditional PVC materials face serious aging problems when used under high temperature conditions. This aging phenomenon is mainly manifested in the decrease of the tensile strength and tensile strain at break of the material, as well as the excessive change rate of tensile strength and tensile strain at break after aging, which greatly affects the service life and safety performance of the charging pile power cable.
[0004] The stabilizer composition used for polyvinyl chloride charging cables in the prior art can improve the heat resistance of PVC materials to a certain extent, but its effect is often unsatisfactory under long-term high-temperature conditions. Traditional stabilizers such as lead salt stabilizers, although they have good thermal stability, have been gradually eliminated due to their high toxicity and serious environmental pollution. Environmentally friendly stabilizers such as calcium zinc stabilizers, although less toxic, still have insufficient stability at high temperatures and cannot meet the high requirements of high-temperature stability for new energy vehicle charging pile power lines.
[0005] Therefore, in response to the above problems, it is necessary to develop a stabilizer composition and a preparation method for a new energy vehicle charging pile power cord. After the polyvinyl chloride charging cable to which the stabilizer composition is added is used for a long time at high temperature, the maximum change rate of the material tensile strength and the tensile strain at break can be controlled within a certain range, thereby meeting the high standard requirements of the new energy vehicle charging pile power cord for high temperature stability and long-term use performance. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, an object of the present invention is to provide a stabilizer composition for a new energy vehicle charging pile power cord and a preparation method thereof, aiming to solve the technical problem that the stabilizer composition used in the existing polyvinyl chloride charging cable cannot meet the high temperature stability of the new energy vehicle charging pile power cord under long-term high temperature use.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A stabilizer composition for a new energy vehicle charging pile power cord, comprising the following components and their mass fractions:
[0009] Hydrotalcite 50-60 parts
[0010] Zinc stearate 10-20 parts
[0011] 3-6 parts of perfluorohexanoic acid modified chitosan
[0012] 1-3 parts of β-diketone
[0013] 10-20 parts of basic metal compound
[0014] 3-7 parts of hindered phenol antioxidant
[0015] Phosphite compounds 0.3-1 part
[0016] 1-3 parts of polyol compounds.
[0017] The mass ratio of the perfluorohexanoic acid modified chitosan and β-diketone is (2-3):1;
[0018] The perfluorohexanoic acid modified chitosan is obtained by reacting perfluorohexanoic acid and chitosan in an organic solvent, dichloromethane;
[0019] The preparation method of perfluorohexanoic acid modified chitosan is specifically as follows: adding perfluorohexanoic acid and chitosan into an organic solvent of dichloromethane, reacting at 30-50° C. for 24-48 hours in the presence of a dehydrating agent EDC·HCl, and obtaining the chitosan after centrifugation, washing with water, and drying.
[0020] The molar ratio of perfluorohexanoic acid to chitosan is (2-3):1; the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:4-6;
[0021] The β-diketone is selected from one or more of stearoylbenzoylmethane, isobutyrylbenzoylmethane and dibenzoylmethane;
[0022] The alkaline metal compound is selected from LiOH, NaOH, KOH, CaO, Ca(OH) 2 、MgO、Mg(OH) 2 、Al(OH) 3 、CaCO 3 and MgCO 3 One or more of;
[0023] The hindered phenol antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 264, and antioxidant 2246;
[0024] The phosphite compound is selected from one or both of triphenyl phosphite and diisodecyl phosphite;
[0025] The polyol compound is selected from one or more of pentaerythritol, dipentaerythritol, tripentaerythritol, trimethylolethane, and di(trimethylol)propane;
[0026] The second object of the present invention is to provide a method for preparing the stabilizer composition for the power cord of a new energy vehicle charging pile, comprising the following preparation steps:
[0027] (1) Weigh the raw materials according to the above formula;
[0028] (2) The weighed raw materials are added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 0.5-1 h to obtain the stabilizer composition.
[0029] The third object of the present invention is to provide a new energy vehicle charging pile polyvinyl chloride cable material, wherein the new energy vehicle charging pile polyvinyl chloride cable material comprises the above-mentioned stabilizer composition.
[0030] The fourth object of the present invention is to provide an application of a stabilizer composition for a new energy vehicle charging pile power cord to improve the high temperature stability of polyvinyl chloride cable materials for new energy vehicle charging piles.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] (1) The inventors creatively add perfluorohexanoic acid-modified chitosan and β-diketone to the formula of the stabilizer composition for the power cord of the new energy vehicle charging pile. On the one hand, the two carbonyl groups of β-diketone are used to generate tautomers to form a stable chelate with the metal zinc ions in zinc stearate to inhibit the dehydrochlorination reaction. On the other hand, the high adsorption effect of the chitosan structure in the perfluorohexanoic acid-modified chitosan on HCl and the structure of chitosan grafted with perfluorohexanoic acid obtained by the reaction of the carboxyl group of perfluorohexanoic acid with the amino group in chitosan are used. This special structure has better chelating ability with metal zinc ions and inhibits the dehydrochlorination due to the electron-withdrawing effect of perfluoroalkane and its excellent thermal stability. The addition of the two together improves the mechanical property stability of polyvinyl chloride cable material after aging.
[0033] (2) The inventors creatively discovered that the perfluorohexanoic acid-modified chitosan and β-diketone added to the formula of the stabilizer composition for the power cord of the new energy vehicle charging pile play a synergistic role. By adjusting the ratio of the two, the high-temperature stability of the polyvinyl chloride cable material after aging is better improved. DETAILED DESCRIPTION
[0034] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0035] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0037] The raw materials are selected as follows:
[0038] Hydrotalcite: Tianjin Xiensi Biochemical Technology Co., Ltd., H-24510;
[0039] Perfluorohexanoic acid: Shanghai Yuanye Biotechnology Co., Ltd., B67162;
[0040] Chitosan: Shanghai MacLean Biochemical Technology Co., Ltd., oligochitosan C909112, Mw 800-1000.
[0041] The β-diketone is selected as dibenzoylmethane.
[0042] The basic metal compound is A1(OH) 3 .
[0043] The hindered phenol antioxidant is selected as antioxidant 1010.
[0044] The phosphite compound is triphenyl phosphite.
[0045] The polyol compound is pentaerythritol.
[0046] Preparation of chitosan modified with perfluorohexanoic acid
[0047] Preparation Example 1
[0048] Preparation of perfluorohexanoic acid modified chitosan F-Chitosan-1:
[0049] Perfluorohexanoic acid and chitosan were added to a container of organic solvent dichloromethane, and then a dehydrating agent EDC·HCl was added, and the mixture was stirred at 50°C for 36 hours, and then centrifuged, washed with water for 3 times, and vacuum dried at 80°C for 30 minutes to obtain;
[0050] The molar ratio of perfluorohexanoic acid to chitosan is 2:1, the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:5; and the amount of dichloromethane added is 10 times the total mass of perfluorohexanoic acid and chitosan.
[0051] Preparation Example 2
[0052] Preparation of perfluorohexanoic acid modified chitosan F-Chitosan-2:
[0053] Perfluorohexanoic acid and chitosan were added to a container of organic solvent dichloromethane, and then a dehydrating agent EDC·HCl was added, and the mixture was stirred at 50°C for 36 hours, and then centrifuged, washed with water for 3 times, and vacuum dried at 80°C for 30 minutes to obtain;
[0054] The molar ratio of perfluorohexanoic acid to chitosan is 3:1, the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:5; and the amount of dichloromethane added is 10 times the total mass of perfluorohexanoic acid and chitosan.
[0055] Preparation Example 3
[0056] Preparation of perfluorohexanoic acid modified chitosan F-Chitosan-3:
[0057] Perfluorohexanoic acid and chitosan were added to a container of organic solvent dichloromethane, and then a dehydrating agent EDC·HCl was added, and the mixture was stirred at 50°C for 36 hours, and then centrifuged, washed with water for 3 times, and vacuum dried at 80°C for 30 minutes to obtain;
[0058] The molar ratio of perfluorohexanoic acid to chitosan is 2:1, the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:4; and the amount of dichloromethane added is 10 times the total mass of perfluorohexanoic acid and chitosan.
[0059] Comparative Preparation Example 1
[0060] Preparation of perfluorohexanoic acid modified chitosan F-Chitosan-C1:
[0061] Perfluorohexanoic acid and chitosan were added to a container of organic solvent dichloromethane, and then a dehydrating agent EDC·HCl was added, and the mixture was stirred at 50°C for 36 hours, and then centrifuged, washed with water for 3 times, and vacuum dried at 80°C for 30 minutes to obtain;
[0062] The molar ratio of perfluorohexanoic acid to chitosan is 1:1, the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:5; and the amount of dichloromethane added is 10 times the total mass of perfluorohexanoic acid and chitosan.
[0063] Comparative Preparation Example 2
[0064] Preparation of perfluorohexanoic acid modified chitosan F-Chitosan-C2:
[0065] Perfluorohexanoic acid and chitosan were added to a container of organic solvent dichloromethane, and then a dehydrating agent EDC·HCl was added, and the mixture was stirred at 50°C for 36 hours, and then centrifuged, washed with water for 3 times, and vacuum dried at 80°C for 30 minutes to obtain;
[0066] The molar ratio of perfluorohexanoic acid to chitosan is 4:1, the molar ratio of perfluorohexanoic acid to dehydrating agent EDC·HCl is 1:5; and the amount of dichloromethane added is 10 times the total mass of perfluorohexanoic acid and chitosan.
[0067] Comparative Preparation Example 3
[0068] Preparation of caproic acid modified chitosan Chitosan-C3:
[0069] Hexanoic acid and chitosan were added to a container containing an organic solvent of dichloromethane, and then a dehydrating agent, EDC·HCl, was added, stirred and reacted at 50°C for 36 hours, centrifuged, washed with water three times, and vacuum dried at 80°C for 30 minutes to obtain;
[0070] The molar ratio of caproic acid to chitosan is 2:1, the molar ratio of caproic acid to dehydrating agent EDC·HCl is 1:5, and the amount of dichloromethane added is 10 times the total mass of caproic acid and chitosan.
[0071] Example 1
[0072] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0073] 50 parts of hydrotalcite
[0074] 15 parts of zinc stearate
[0075] Perfluorohexanoic acid modified chitosan F-Chitosan-1 6 parts
[0076] 2 parts of dibenzoylmethane
[0077] A1(OH) 3 15 servings
[0078] Antioxidant 1010 3 parts
[0079] 1 part of triphenyl phosphite
[0080] 1 part of pentaerythritol.
[0081] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0082] Example 2
[0083] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0084] 50 parts of hydrotalcite
[0085] 15 parts of zinc stearate
[0086] Perfluorohexanoic acid modified chitosan F-Chitosan-2 6 parts
[0087] 2 parts of dibenzoylmethane
[0088] A1(OH) 3 15 servings
[0089] Antioxidant 1010 3 parts
[0090] 1 part of triphenyl phosphite
[0091] 1 part of pentaerythritol.
[0092] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0093] Example 3
[0094] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0095] 50 parts of hydrotalcite
[0096] 15 parts of zinc stearate
[0097] Perfluorohexanoic acid modified chitosan F-Chitosan-3 6 parts
[0098] 2 parts of dibenzoylmethane
[0099] A1(OH) 3 15 servings
[0100] Antioxidant 1010 3 parts
[0101] 1 part of triphenyl phosphite
[0102] 1 part of pentaerythritol.
[0103] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0104] Example 4
[0105] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0106] 50 parts of hydrotalcite
[0107] 15 parts of zinc stearate
[0108] Perfluorohexanoic acid modified chitosan F-Chitosan-1 6 parts
[0109] 3 parts of dibenzoylmethane
[0110] A1(OH) 3 15 servings
[0111] Antioxidant 1010 3 parts
[0112] 1 part of triphenyl phosphite
[0113] 1 part of pentaerythritol.
[0114] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0115] Example 5
[0116] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0117] 50 parts of hydrotalcite
[0118] 15 parts of zinc stearate
[0119] Perfluorohexanoic acid modified chitosan F-Chitosan-1 4 parts
[0120] 2 parts of dibenzoylmethane
[0121] A1(OH) 3 15 servings
[0122] Antioxidant 1010 3 parts
[0123] 1 part of triphenyl phosphite
[0124] 1 part of pentaerythritol.
[0125] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0126] Example 6
[0127] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0128] 60 parts of hydrotalcite
[0129] 20 parts of zinc stearate
[0130] Perfluorohexanoic acid modified chitosan F-Chitosan-1 6 parts
[0131] 2 parts of dibenzoylmethane
[0132] A1(OH) 3 15 servings
[0133] Antioxidant 1010 3 parts
[0134] 1 part of triphenyl phosphite
[0135] 1 part of pentaerythritol.
[0136] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0137] Comparative Example 1
[0138] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0139] 50 parts of hydrotalcite
[0140] 15 parts of zinc stearate
[0141] 8 parts of dibenzoylmethane
[0142] A1(OH) 3 15 servings
[0143] Antioxidant 1010 3 parts
[0144] 1 part of triphenyl phosphite
[0145] 1 part of pentaerythritol.
[0146] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0147] Comparative Example 2
[0148] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0149] 50 parts of hydrotalcite
[0150] 15 parts of zinc stearate
[0151] Perfluorohexanoic acid modified chitosan F-Chitosan-1 8 parts
[0152] A1(OH) 3 15 servings
[0153] Antioxidant 1010 3 parts
[0154] 1 part of triphenyl phosphite
[0155] 1 part of pentaerythritol.
[0156] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0157] Comparative Example 3
[0158] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0159] 50 parts of hydrotalcite
[0160] 15 parts of zinc stearate
[0161] Perfluorohexanoic acid modified chitosan F-Chitosan-1 3 parts
[0162] 3 parts of dibenzoylmethane
[0163] A1(OH) 3 15 servings
[0164] Antioxidant 1010 3 parts
[0165] 1 part of triphenyl phosphite
[0166] 1 part of pentaerythritol.
[0167] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0168] Comparative Example 4
[0169] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0170] 50 parts of hydrotalcite
[0171] 15 parts of zinc stearate
[0172] Perfluorohexanoic acid modified chitosan F-Chitosan-1 6 parts
[0173] 1.5 parts of dibenzoylmethane
[0174] A1(OH) 3 15 servings
[0175] Antioxidant 1010 3 parts
[0176] 1 part of triphenyl phosphite
[0177] 1 part of pentaerythritol.
[0178] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0179] Comparative Example 5
[0180] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0181] 50 parts of hydrotalcite
[0182] 15 parts of zinc stearate
[0183] Perfluorohexanoic acid modified chitosan F-Chitosan-C1 6 parts
[0184] 2 parts of dibenzoylmethane
[0185] A1(OH) 3 15 servings
[0186] Antioxidant 1010 3 parts
[0187] 1 part of triphenyl phosphite
[0188] 1 part of pentaerythritol.
[0189] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0190] Comparative Example 6
[0191] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0192] 50 parts of hydrotalcite
[0193] 15 parts of zinc stearate
[0194] Perfluorohexanoic acid modified chitosan F-Chitosan-C2 6 parts
[0195] 2 parts of dibenzoylmethane
[0196] A1(OH) 3 15 servings
[0197] Antioxidant 1010 3 parts
[0198] 1 part of triphenyl phosphite
[0199] 1 part of pentaerythritol.
[0200] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0201] Comparative Example 7
[0202] Preparation of a stabilizer composition for a new energy vehicle charging pile power cord, weighing raw materials according to the following components and their mass fractions:
[0203] 50 parts of hydrotalcite
[0204] 15 parts of zinc stearate
[0205] Hexanoic acid modified chitosan Chitosan-C3 6 parts
[0206] 2 parts of dibenzoylmethane
[0207] A1(OH) 3 15 servings
[0208] Antioxidant 1010 3 parts
[0209] 1 part of triphenyl phosphite
[0210] 1 part of pentaerythritol.
[0211] The weighed raw materials were added into a high-speed mixer at a rotation speed of 1000 rpm and mixed for 1 hour to obtain the stabilizer composition.
[0212] Sample preparation and performance testing:
[0213] The stabilizer compositions of Examples 1-6 and Comparative Examples 1-7 were used to prepare polyvinyl chloride cable materials according to the following formula (parts by mass):
[0214] SG-5 polyvinyl chloride Stabilizer composition Diisodecyl phthalate Epoxidized soybean oil 100 5 40 5
[0215] According to GB / T 1040.3-2006, test method for tensile properties of plastics, polyvinyl chloride cable materials before and after aging were tested.
[0216] Aging conditions: test temperature 150±2℃ test time, 240h.
[0217] The test results are shown in Table 1-2 below:
[0218] Table 1
[0219]
[0220] Table 2
[0221]
[0222]
[0223] By comparing Examples 1-6 with Comparative Examples 1-7, it can be seen that the stabilizer composition of the present invention is added with a specific proportion of perfluorohexanoic acid-modified chitosan and β-diketone, and is combined with hydrotalcite, zinc stearate, alkaline metal compounds, antioxidants and polyol compounds, so that the polyvinyl chloride cable material to which the stabilizer composition is added has a tensile strength of >16MPa after an aging test at 150°C for 240h, and the maximum change rate of the tensile strength is controlled within ±15, the tensile strain at break is >140%, and the maximum change rate of the tensile strain at break is controlled within ±18, which can well meet the stability requirements of the power cord of the new energy vehicle charging pile under long-term high temperature outdoors.
[0224] By comparing Examples 1-6 with Comparative Examples 1-2, it can be seen that the perfluorohexanoic acid-modified chitosan and β-diketone added to the stabilizer composition of the present invention play a synergistic role, so that the final polyvinyl chloride cable material maintains good mechanical property stability after aging test.
[0225] By comparing Examples 1-6 with Comparative Examples 3-4, it can be seen that when the ratio of perfluorohexanoic acid-modified chitosan and β-diketone added to the stabilizer composition does not meet the requirements of the present invention, the mechanical property stability of the thermal aging performance of the finally obtained polyvinyl chloride cable material decreases rapidly.
[0226] By comparing Examples 1-6 with Comparative Examples 5-6, it can be seen that when the ratio of perfluorohexanoic acid and chitosan does not meet the requirements of the present invention during the preparation of the perfluorohexanoic acid-modified chitosan added to the stabilizer composition, the amino group of chitosan reacts to different degrees with the carboxyl group of perfluorohexanoic acid, resulting in a rapid decrease in the mechanical properties stability of the thermal aging performance of the finally obtained polyvinyl chloride cable material.
[0227] By comparing Examples 1-6 with Comparative Example 7, it can be seen that when the stabilizer composition does not use fluorine-free caproic acid-modified chitosan, the thermal stability of the polyvinyl chloride cable material finally obtained is poor. This may be because the modified chitosan in the fluorine-containing caproic acid improves the chelating effect on zinc ions, and while the chitosan absorbs HCl, the dehydrochlorination reaction is inhibited.
[0228] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention rather than to limit them. Although the embodiments of the present invention have been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the embodiments of the present invention can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A stabilizer composition for a new energy vehicle charging pile power line, characterized in that: It includes the following components and their mass fractions: Hydrotalcite 50-60 parts Zinc stearate 10-20 parts 3-6 parts of perfluorohexanoic acid modified chitosan 1-3 parts of β-diketone 10-20 parts of basic metal compound 3-7 parts of hindered phenol antioxidant Phosphite compounds 0.3-1 part 1-3 parts of polyol compounds; Wherein, the mass ratio of perfluorohexanoic acid-modified chitosan and β-diketone is (2-3):1; The perfluorohexanoic acid modified chitosan is obtained by reacting perfluorohexanoic acid and chitosan in an organic solvent, dichloromethane; The preparation method of the perfluorohexanoic acid modified chitosan is specifically as follows: adding perfluorohexanoic acid and chitosan into an organic solvent of dichloromethane, reacting at 30-50° C. for 24-48 hours in the presence of a dehydrating agent EDC·HCl, centrifuging, washing with water, and drying to obtain; The molar ratio of perfluorohexanoic acid to chitosan is (2-3):
1.
2. The stabilizer composition according to claim 1, characterized in that The β-diketone is selected from one or more of stearoylbenzoylmethane, isobutyrylbenzoylmethane and dibenzoylmethane; The alkaline metal compound is selected from one or more of LiOH, NaOH, KOH, CaO, Ca(OH)2, MgO, Mg(OH)2, Al(OH)3, CaCO3 and MgCO3; The hindered phenol antioxidant is selected from one or more of antioxidant 1010, antioxidant 1076, antioxidant 264, and antioxidant 2246; The phosphite compound is selected from one or both of triphenyl phosphite and diisodecyl phosphite; The polyol compound is selected from one or more of pentaerythritol, dipentaerythritol, tripentaerythritol, trimethylolethane, and di(trimethylol)propane.
3. The stabilizer composition according to claim 2, characterized in that The molar ratio of perfluorohexanoic acid to the dehydrating agent EDC·HCl is 1:4-6.
4. A method for preparing a stabilizer composition for a new energy vehicle charging pile power line according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following preparation steps: (1) Weigh the raw materials according to the formula of claim 1; (2) Add the weighed raw materials into a high-speed mixer at a rotation speed of 1000 rpm and mix for 0.5-1 hour to obtain the stabilizer composition.
5. A polyvinyl chloride cable material for a new energy vehicle charging pile, characterized in that: The polyvinyl chloride cable material for the new energy vehicle charging pile includes the stabilizer composition described in any one of claims 1 to 3 or the stabilizer composition prepared by the preparation method described in claim 4.
6. Use of a stabilizer composition for a new energy vehicle charging pile power line according to any one of claims 1 to 3 or a stabilizer composition prepared by the preparation method of claim 4 in improving the high temperature stability of polyvinyl chloride cable materials for new energy vehicle charging piles.
Citation Information
Patent Citations
Application of fluorine-containing compound modified chitosan in preparation of transdermal delivery preparation
CN111848835A
Charge-bearing cyclodextrin polymeric materials and methods of making and using same
CN114015127A